Intercultural Personhood - Vu Hao, Nguyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Personhood is one of the key problems not only in philosophy and the sciences, but also in different fields of the social life in all countries of the world. The solution of this problem is the starting-point for various further problems concerning personhood’s metaphysical, physical, moral and legal aspects, e.g. discussions in biomedical ethics about abortion, stem-cell research, euthanasia or debates in philosophy and law about human rights, citizenship, equality, liberty, legal person, corporate personhood, etc. On the one hand, it is necessary to give universal criteria of personhood to distinguish between human beings and animals, between persons and potential persons, between diverse degrees of personhood. On the other hand, it is also important to consider special criteria of personhood that apply within and between different cultures, what might be called intercultural criteria of personhood. This paper offers some reflections on intercultural personhood, its criteria, and possible problems and solutions, particularly in the contemporary context of globalization. Received: 25th January 2016; Revised: 31st March 2016; Accepted: 6th April 2016